Implementasi Metode Ephemeral Diffie Hellman Over Cose (EDHOC) pada Wireless Sensor Network (WSN) sebagai Mekanisme Autentikasi berbasis Modul Komunikasi LoRa - I Gede Wahyu Sanjaya; Adhitya Bhawiyuga; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In general WSN can be build with one node and one gateway. Comunication between node sensor and gateway using other device that support wireless network as bridge such as LoRa. WSN with LoRa does not have authentication system. If considering in few years, system without continous authentication also has a big risk so that is became a requirement to have countinous authentiction. With countinouse authentication node and gateway can still recognize their valid pair. Give more protection while comunicating. Use Ephemeral Diffie Hellman Over COSE (EDHOC) method as alternatif solution for fixing problem with key management approach. For reducing other party or illegal attacker probability of sniffing and eavesdropping while communicating. The result of this research found out system generate new key based on time configuration that already set for updating key authentication. Other than that performance system after applying countinous authentication has a significant effect such as does not impact delivery time and giving extra protection while communicating.